Anti-Alzheimer Activity of Combinations of Cocoa with Vinpocetine or Other Nutraceuticals in Rat Model: Modulation of Wnt3/β-Catenin/GSK-3β/Nrf2/HO-1 and PERK/CHOP/Bcl-2 Pathways - Karema Abu-Elfotuh; Amina M. A. Tolba; Furqan H. Hussein; Ahmed M. E. Hamdan; Mohamed A. Rabeh; Saad A. Alshahri; Azza A. Ali; Sarah M. Mosaad; Nihal A. Mahmoud; Magdy Y. Elsaeed; Ranya M. Abdelglil; Rehab R. El-Awady; et al. (MDPI AG, 2023)
Alzheimer's disease (AD) is a devastating illness with limited therapeutic interventions. The aim of this study is to investigate the pathophysiological mechanisms underlying AD and explore the potential neuroprotective effects of cocoa, either alone or in combination with other nutraceuticals, in an animal model of aluminum-induced AD. Rats were divided into nine groups: control, aluminum chloride (AlCl3) alone, AlCl3 with cocoa alone, AlCl3 with vinpocetine (VIN), AlCl3 with epigallocatechin-3-gallate (EGCG), AlCl3 with coenzyme Q10 (CoQ10), AlCl3 with wheatgrass (WG), AlCl3 with vitamin (Vit) B complex, and AlCl3 with a combination of Vit C, Vit E, and selenium (Se). The animals were treated for five weeks, and we assessed behavioral, histopathological, and biochemical changes, focusing on oxidative stress, inflammation, Wnt/GSK-3β/β-catenin signaling, ER stress, autophagy, and apoptosis. AlCl3 administration induced oxidative stress, as evidenced by elevated levels of malondialdehyde (MDA) and downregulation of cellular antioxidants (Nrf2, HO-1, SOD, and TAC). AlCl3 also upregulated inflammatory biomarkers (TNF-α and IL-1β) and GSK-3β, leading to increased tau phosphorylation, decreased brain-derived neurotrophic factor (BDNF) expression, and downregulation of the Wnt/β-catenin pathway. Furthermore, AlCl3 intensified C/EBP, p-PERK, GRP-78, and CHOP, indicating sustained ER stress, and decreased Beclin-1 and anti-apoptotic B-cell lymphoma 2 (Bcl-2) expressions. These alterations contributed to the observed behavioral and histological changes in the AlCl3-induced AD model. Administration of cocoa, either alone or in combination with other nutraceuticals, particularly VIN or EGCG, demonstrated remarkable amelioration of all assessed parameters. The combination of cocoa with nutraceuticals attenuated the AD-mediated deterioration by modulating interrelated pathophysiological pathways, including inflammation, antioxidant responses, GSK-3β-Wnt/β-catenin signaling, ER stress, and apoptosis. These findings provide insights into the intricate pathogenesis of AD and highlight the neuroprotective effects of nutraceuticals through multiple signaling pathways.